Handbook on the economics of the Internet - Bauer, Johannes; Latzer, Michael (Cheltenham, UK Edward Elgar Publishing, 2016)
This handbook brings together twenty-six original chapters that discuss theoretical and applied frameworks for the study of the economics of the Internet, encompassing: its unique economics as a global information and communications infrastructure, the effects of the Internet on economic transactions, including social production, advertising, innovation, and intellectual property rights, the economics and management of Internet-based industries, such as search, news, entertainment, culture, and virtual worlds, and the effects of the Internet on the economy at large.
1. The economics of the internet:an overview /Johannes M. Bauer and Michael Latzer.-- 2. The industrial organization of the internet / Gunter Knieps and Johannes M. Bauer.-- The internet as a complex layered system / Stephen J. Schultze and Richard S. Whitt.-- A network science approach to the internet / Volker Schneider and Johannes M. Bauer.-- Peer production and cooperation / Yochai Benkler.-- 6. The internet and productivity / Carol Corrado and Bart van Ark.-- 7. Cultural economics and the internet / Christian Handke,Paul Stepan and Ruth Towse.-- A political economy approach to the internet / Patricia Mazepa and Vincent Mosco.-- 9. Competition and antitrust in internet markets / Justus Haucup and Torben Stuhmeir.-- 10. The economics of internet standards /Stanley M. Besen and George Sadowsky.-- The economics of copyright and the internet /Sacha Wunsch - Vincent.-- 12. The economics of privacy,data protection and surveillance /Ian Brown.-- 13. Economics of cybersecurity / Hadi Asghari,Michel van Eeten and Johannes M. Bauer.-- 14. Internet architecture and innovation in applications / Barbara van schewick.-- 15. Organizational innovations,ICTs and knowledge governance : the case of platforms.-- 16 Interconnection in the internet:peering,interoperability and content delivery / David D. Clark,William H. Lehr and Steven Bauer.-- 17.Internet business strategies / Johann J. Kranz and Arnold Picot.-- 18. The economics of internet search.-- 19. The economics of algorithmic selection on the internet / Michael Latzer,Katharina Hollnbuchner,Natascha Just and Florian Saurwein.-- 20. Online advertising economics / Wejuan Ma and Steven S. Wildman.-- 21. Online news / Lucy Kung, Nic Newman and Robert G. Picard.-- 22. The economics of online video entertainment /Ryland Sherman and David Waterman.-- 23. Business strategies and revenue models for converged video services / Yu-Li-Liu.-- 24.The economics of virtual worlds /Isaac knowles and edward Castronova.-- 25. Economics of big data / Claudio Feijo,Jose -Luis Gomez-Barroso and Shivom Aggarwal.-- 26. The evolution of the internet: a socioeconomic account / D. Linda Garcia.-- 27. From the internet of science to the internet of entertainment / Eli M. Noam.
Includes bibliographical references and index.
Keywords: Technological innovations -- Economic aspects; Internet -- Economic aspects; Internet -- Economic aspects